The Topic of Death in the Literary Discourse of Kosovo - Visoka, Avdi; Krasniqi, Nysret (Journal of History Culture and Art Research, 2018)
We will hereby analyse religiosity as a matrix and phenomenon of literary creative philosophy. Furthermore, we will discuss the influence of this matrix in Kosovan literary discourse, whether folk or authorial. The research will not include discussion of the doctrines, but the topic that emanates from them, which subsequently turns into literary discourse, whether symbolic-metonymic or metaphorical-allegorical, making the religiosity its distinctive aesthetics. In this chain of models, we will treat the ballad and poetic elements, as works of Albanian literature. This will create a view of the dominance of religion in them, nonetheless, it will likewise help investigate the differences regarding authorial access to religion, whether observed as faith or as a culture. Similarly, we will focus on the study of this martyrdom in the plan of discursive crossings from their presence, as rhapsodic songs in written texts or manuscripts, known as texts of Aljamiado.